Ant Community Structure in Palm Oil Plantation Bordering Secondary Forest - Arlen Hasan; siska efendi; Yaherwandi Yaherwandi; Awaluddin Awaluddin (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2023)
Deforestation or functional change from forest to non-forest plays a role in changing ecosystems and species within it. Insects as one of the faunas in it is an interesting aspect to be studied, especially ants. The research was conducted in Nagari Gunung Selasih and Sungai Kambut, Pulau Punjung District, Dharmasraya Regency, West Sumatra from November 2017 to January 2018. This study aims to determine the diversity of ants in the palm oil plantation ecosystem bordering the forest ecosystem. This research takes the form of a survey where the Purposive Random Sampling method was used for points sampling. Hand Collecting, Bait Trap, and Pitfall Trap sampling methods were applied for each plant. Identification of the samples obtained was carried out at the Animal Taxonomy Laboratory, Department of Biology, Faculty of Mathematics and Natural Sciences, Andalas University, Padang. Total ants (Hymenoptera: Formicidae) collected during the study were 3,046 individuals consisting of 5 subfamilies, 15 genera, and 29 species. The most dominant species was Anoplolepis graciliphes, followed by Odontoponera denticulate and Odontomachus simillimus. Based on the results of the study, it can be concluded that the level of abundance and diversity of ant species is not directly affected by the distance from the forest ecosystem, but it is strongly influenced by the composition of environmental factors such as temperature, humidity, light intensity, altitude, and management of existing habitats and vegetation.